Thorn Bug, Umbonia crassicornis (Amyot and Serville) (Insecta: Hemiptera: Membracidae) - Frank W. Mead (EDIS)
Revised! This document is EENY-175 (originally published as DPI Entomology Circular 8), part of the Featured Creatures collection. Published by the Entomology and Nematology Department, UF/IFAS Extension, August 2004.